Harold L. Ickes papers - Ickes, Harold L. (Harold LeClair), 1874-1952.
Correspondence, diaries, speeches and writings, family papers, legal and financial records, subject files, scrapbooks, and other papers documenting all aspects of Ickes's career especially his service as U.S. secretary of the interior. Subjects include the Franklin D. Roosevelt presidential administration; presidential elections (1916-1948); Progressive Party politics; Chicago, Ill., and Illinois state politics; municipal reform; Ickes's Chicago law practice; the Arabian-American Oil Company; conservation; Indian affairs; Japanese-Americans during World War II; oil policy; and Puerto Rico.
Individuals represented include Oscar L. Chapman, James M. Cox, Paul H. Douglas, James A. Farley, James Rudolph Garfield, Will H. Hays, Charles Evans Hughes, Samuel Insull, Hiram Johnson, Lyndon B. Johnson, Frank Knox, Henry Morgenthau, Gifford Pinchot, Donald R. Richberg, Raymond Robins, Franklin D. Roosevelt, Theodore Roosevelt, Harry S. Truman, Karl D. Vittum, Henry A. Wallace, and William Allen White.
Microfilm edition of diaries (1933-1951) and index to diaries available
Microfilm edition of memoirs (containers 432-444) available
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Lawyer and U.S. secretary of the interior.
Collection material in English.
Keywords: Chapman, Oscar L. -- 1896-1978.; Cox, James M. -- 1870-1957.; Douglas, Paul H. -- 1892-1976.; Farley, James A. -- 1888-1976.; Garfield, James Rudolph, -- 1865-1950.; Hays, Will H. -- 1879-1954.; Hughes, Charles Evans, -- 1862-1948.; Insull, Samuel, -- 1859-1938.; Johnson, Hiram, -- 1866-1945.; Johnson, Lyndon B. -- 1908-1973.; Knox, Frank, -- 1874-1944.; Morgenthau, Henry, -- 1891-1967.; Pinchot, Gifford, -- 1865-1946.; Richberg, Donald R. -- 1881-1960.; Robins, Raymond, -- 1873-1954.; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Theodore, -- 1858-1919.; Truman, Harry S., -- 1884-1972.; Vittum, Karl D; Wallace, Henry A. -- 1888-1965.; White, William Allen, -- 1868-1944.; United States. -- Department of the Interior; Arabian American Oil Company; Progressive Party (1912); Conservation of natural resources; Indians of North America -- Government relations; Municipal government -- United States; Petroleum industry and trade; Practice of law -- Illinois -- Chicago; Presidents -- United States -- Election; World War, 1939-1945 -- Japanese Americans; Chicago (Ill.) -- Politics and government; Illinois -- Politics and government; Puerto Rico -- History; United States -- History -- 1933-1945.; United States -- Politics and government -- 1933-1945.; Cabinet officers; Lawyers